Shaping urban consolidation debates: Social representations in Brisbane newspaper media. (May 2017) - Raynor, Katrina; Matthews, Tony; Mayere, Severine
Recent international trends towards urban consolidation, intended to reduce outward urban sprawl by concentrating growth within existing neighbourhoods, can cause contention in cities. Understanding how the mass media represents urban consolidation can lead to more informed and democratic planning practices. This paper employs Social Representations Theory to identify and understand representations of urban consolidation in newspaper media. The theory recognises that the media is a key purveyor of public discourse and can reflect, shape or suppress ideas circulating in society. This novel approach has not previously been applied to understanding social representations of urban consolidation strategies in the mass media. The rapidly growing and changing city of Brisbane, Australia, is utilised as a case study. Brisbane is situated in South East Queensland, the fastest growing region in Australia, and is governed by regional and local planning policies that strongly support increased densities in existing urban areas. Findings from a quantitative textual analysis of 449 articles published in Brisbane newspapers between 2007 and 2014 reveal key clusters and classes of co-occurring words that represent dominant social representations apparent in the newspaper corpus. The paper provides two key conclusions. The first is that social representations occurring in mass media represent an important source of information about 'common sense' understandings and evaluations of urban consolidation debates. The second is that urban consolidation is represented as a multifaceted issue, including interrelated themes of housing, sustainable population growth, investment strategies and the interplay between politics and planning.